Improvement of cob thermal inertia by latent heat storage and its implication on energy consumption. (25th April 2022) - Alassaad, Farjallah; Touati, Karim; Levacher, Daniel; Mendili, Yassine El; Sebaibi, Nassim
Highlights: Introduction of phase change materials (PCM) into cob. Improvement of cob thermal properties with PCMs incorporation. Degradation of cob hygroscopic and mechanical properties with PCMs incorporation. Reduction of energy consumption in cob house incorporating PCMs in their walls. Abstract: Climate change imposes new guidelines on our planet. Due to its impact on the environment, construction industry must invest in the development of new building solutions or the improvement of the existing ones. Thus, many new materials are emerging, while old construction techniques are being reconsidered in order to improve their performances. Earth-based construction techniques are viable solutions. Such techniques and materials offer many advantages, but their full-scale use, while respecting actual standards, remains limited. Considering cob, the objective of present study is to improve this material's thermal properties through phase change materials (PCM) incorporation. Mechanical, hygrometric, and thermal experimental studies were performed on soil-fiber-PCM mixtures. While the incorporation of PCMs showed a clear improvement of cob thermal properties (insulation and inertia), a deterioration of its hygrometric and mechanical properties is observed. Furthermore, energy consumption of a typical house has been estimated by considering cob with different PCM content within its external walls. Finally, an optimum phase change temperature adapted to the Normandy climate has been proposed.